Sound source localization method in an environment with flow based on Amiet–IMACS. (1st May 2017) - Wei, Long; Li, Min; Qin, Sheng; Fu, Qiang; Yang, Debin
Abstract: A sound source localization method is proposed to localize and analyze the sound source in an environment with airflow. It combines the improved mapping of acoustic correlated sources (IMACS) method and Amiet's method, and is called Amiet–IMACS. It can localize uncorrelated and correlated sound sources with airflow. To implement this approach, Amiet's method is used to correct the sound propagation path in 3D, which improves the accuracy of the array manifold matrix and decreases the position error of the localized source. Then, the mapping of acoustic correlated sources (MACS) method, which is as a high-resolution sound source localization algorithm, is improved by self-adjusting the constraint parameter at each irritation process to increase convergence speed. A sound source localization experiment using a pair of loud speakers in an anechoic wind tunnel under different flow speeds is conducted. The experiment exhibits the advantage of Amiet–IMACS in localizing a more accurate sound source position compared with implementing IMACS alone in an environment with flow. Moreover, the aerodynamic noise produced by a NASA EPPLER 862 STRUT airfoil model in airflow with a velocity of 80 m/s is localized using the proposed method, which further proves its effectiveness in a flow environment. Finally, the relationship between the source position of this airfoil model and its frequency, along with its generation mechanism, is determined and interpreted. Graphical abstract: Highlights: The proposed Amiet–IMACS method can localize sound source in environment with flow. Array manifold matrix error caused by flow in 3D is corrected using Amiet's method. MACS is improved by self-adjusting constraint parameter to make it converge faster. Sound source localization of two speakers is conducted in an anechoic wind tunnel. The aerodynamic noise source of an airfoil model is localized and analyzed.